1996
DOI: 10.1080/00365519609090602
|View full text |Cite
|
Sign up to set email alerts
|

Is nitric oxide and heparin treatment justified in inflammatory bowel disease? An experimental study

Abstract: Microcirculatory disturbances of the colon may contribute to the pathogenesis of inflammatory bowel disease. The aim of the study was to investigate the alterations of rectal blood perfusion in experimental colitis with reference to nitric oxide and heparin treatment. The study was carried out on 36 rats, divided into six groups: group I, control; group II, control + NG-nitro-L-arginine (L-NNA); group III, colitis without treatment; group IV, colitis + L-arginine; group V, colitis + L-NNA; group VI, colitis + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Expression of NOS-2 in the colon epithelium, particularly in the apical region, in UC is compatible with some protective function of NOS for the injured epithelium. This idea is supported, on one hand, by development of exacerbated UC in NOS-2-de cient mice (33) or in mice treated with NOS-2 inhibitor (34), and, on the other hand, enhanced antiin ammatory effect of the NO-releasing derivative of 5-ASA (35). Induction of NOS-2 in the apical epithelium may also be a cause for inhibited bacterial invasion in UC (36).…”
Section: Discussionmentioning
confidence: 86%
“…Expression of NOS-2 in the colon epithelium, particularly in the apical region, in UC is compatible with some protective function of NOS for the injured epithelium. This idea is supported, on one hand, by development of exacerbated UC in NOS-2-de cient mice (33) or in mice treated with NOS-2 inhibitor (34), and, on the other hand, enhanced antiin ammatory effect of the NO-releasing derivative of 5-ASA (35). Induction of NOS-2 in the apical epithelium may also be a cause for inhibited bacterial invasion in UC (36).…”
Section: Discussionmentioning
confidence: 86%
“…However, a more comprehensive review of the literature reveals that the results of NOS inhibition in the TNBS model are not all 100% protective. Studies range from almost complete protection (100%)16 21 to partial protection,15 19selective regional protection,22 no protection9, and exacerbation of injury 2324 For example, unlike the generalised inhibition of inflammation reported by some investigators, Hogaboam and colleagues22 reported that inhibition of NOS in TNBS induced colitis dramatically reduced neutrophil and macrophage infiltration into the intestine and intestinal hyperplasia (by >90%) but failed to reduce anorexia, smooth muscle hypertrophy, or myenteric nerve dysfunction.…”
Section: Oral L-name Why Is It Beneficial?mentioning
confidence: 99%
“…The ability of heparin to inhibit neutrophil activation, adhesion, and chemotaxis was also found in a mouse model of inflammatory bowel disorder [130,131] , suggesting that balanced interactions between mast cells and neutrophils might be important for the development of IBD. In rat models of IBD, heparin revealed its ability to attenuate TNFα induced leucocyte rolling and CD11b dependent adhesion [132] , reduce serum IL-6 level and improve microcirculatory disturbance in rectal walls [133,134] . Thus, preformed mast cell mediators seemed to have dual actions on the pathogenesis of IBD.…”
Section: Involvement Of Heparin In Pathogenesis Of Ibdmentioning
confidence: 99%